Inventory of Weeds in Mexican Park, Bogor Botanical Garden - Hatipah Salamah; Evi Muliyah; Muhammad Rifqi Hariri (Institut Pertanian Bogor, 2025)
The Bogor Botanical Gardens' Mexican Park presents various dry-climate plants useful for recreation and learning. The presence of weeds in the collection site would have a negative impact because they can inhibit the growth of the collection plants. This study examined the diversity of weeds in the Mexican Park, Bogor Botanical Gardens. This descriptive study took place in the Bogor Botanical Gardens, specifically in the Mexican Park, and weed identification was carried out at the National Research and Innovation Agency. The weed data obtained was then analyzed descriptively through a literature study. The results showed that there were 52 weed species from 28 families. Most species came from the Asteraceae and Araceae families. The block that had the most weeds was Block II.O.IV, with a total of 15 weed species. The species that were often found in each area of the Mexican Garden Collection include Euphorbia graminea Jacq., Euphorbia heterophylla L., Calliandra calothyrsusMeisn, Coleus monostachyus (P. Beauv.) AJ Paton, Cecropia peltate L., and Cissus verticillata subsp. verticillata. Keywords: Inventory, Weeds, Mexican Park, Bogor Botanical Garden